Can we improve how we learn? Investigating learning and transfer of abstract relational principles - Krusche, Moritz (Student Undergraduate Research E-journal!, 2016)
Evidence from both educational and cognitive psychology shows that people have trouble learning abstract relational principles and applying them to different contexts. Participants (N=84) learned to categorise stimuli consisting of abstract coloured patterns organised within either a classification or an inference presentation. They could do so using similarity of features or a relational principle, but only the latter was applicable to the transfer task. Results suggest that inference learning suppressed the ability to consistently encode features and lead to more consistent use of the relational rule and subsequently higher transfer performance, in spite of unchanged contextual richness.